Introduction of Methods Showcase Articles in Language Learning. Issue 1 (14th February 2020) - Crossley, Scott; Marsden, Emma; Ellis, Nick; Kormos, Judit; Morgan‐Short, Kara; Thierry, Guillaume
Abstract: Building on initiatives to promote high quality methodologies and Open Science practices in the language sciences, Language Learning will introduce, as of March 2020, a new manuscript type entitled Methods Showcase Articles (MSAs). The purpose of MSAs is to introduce new or emerging qualitative and quantitative methods, techniques, or instrumentation for language data collection, cleaning, sampling, coding, scoring, and analysis. MSAs are intended to describe methods and provide detailed examples of their application such that language researchers can easily adopt or adapt them in future studies. In this editorial, we outline the goals, format, and benefits of MSAs, discuss how they can advance language sciences, and discuss potential concerns.